2022
DOI: 10.1161/circresaha.120.317107
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variants Contribute to Risk of Transposition of the Great Arteries

Abstract: Background: Dextro-transposition of the great arteries (D-TGA) is a severe congenital heart defect which affects approximately 1 in 4,000 live births. While there are several reports of D-TGA patients with rare variants in individual genes, the majority of D-TGA cases remain genetically elusive. Familial recurrence patterns and the observation that most cases with D-TGA are sporadic suggest a polygenic inheritance for the disorder, yet this remains unexplored. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…Lee et al (20) suggested chromosomal microarray analysis as an effective tool to detect chromosomal copy number variation in fetuses with D-TGA and to improve prenatal counseling, postnatal management, and neurodevelopmental outcomes. Skoric-Milosavljevic et al (21) identified a susceptibility locus at 3p14.3, which is known for its important role in cardiac development. Of note, there exist suspect that D-TGA is polygenic inheritance (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (20) suggested chromosomal microarray analysis as an effective tool to detect chromosomal copy number variation in fetuses with D-TGA and to improve prenatal counseling, postnatal management, and neurodevelopmental outcomes. Skoric-Milosavljevic et al (21) identified a susceptibility locus at 3p14.3, which is known for its important role in cardiac development. Of note, there exist suspect that D-TGA is polygenic inheritance (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic data were generated using the Illumina Human-OmniExpress beadchip (genotyping at ~700.000 SNPs) and quality control was performed as described previously [16] (Supplementary methods).…”
Section: Genetic Analysismentioning
confidence: 99%
“…10 Further, contributions from common variants toward the development of certain CHD subtypes, including transposition of the great arteries and other complex disease, have been highlighted. 11,12 In this edition of Circulation: Genomics and Precision Medicine, Jang et al 13 evaluate noncoding variants near canonical splice sites and their potential to disrupt RNA processing resulting in CHD. Using a combination of computational and in vitro (minigene) assays, they identified 53 de novo variants and 74 rare variants resulting in aberrant splicing in a cohort of 4474 CHD probands from the Pediatric Cardiac Genomics Consortium.…”
Section: See Article By Jang Et Almentioning
confidence: 99%
“…A significant portion of the remaining unsolved cases are hypothesized to result from complex interactions between multiple genetic/epigenetic changes and factors affecting the fetal-placental-maternal environment. Polygenic contributions and the risks associated with disease development 11 and immediate postoperative and long-term outcomes 18 in patients with CHD (ie, polygenic risk scores) are emerging as additional disease contributors; and the large, genotype-phenotype cohorts required to facilitate studies with appropriate statistical power to identify significant disease associations are being further refined. 19 However, there is still much work to be done in understanding the dark matter of the genome, that is, the noncoding regions, and the likely contribution of these hidden culprits to CHD development.…”
Section: See Article By Jang Et Almentioning
confidence: 99%
See 1 more Smart Citation